Stiff Knee Gait After Stroke: The Potential Compensatory Role of Mid‐Swing Rectus Femoris Activity - van Oorschot, Wieneke; Bloks, Bente; Kamphuis, Jip; Pieterse, Allan; Geurts, Alexander; Keijsers, Noël; Nonnekes, Jorik (Case reports in neurological medicine, 2025)
Reduced knee flexion during the swing phase of gait, commonly referred to as ‘stiff knee gait,’ is frequently encountered in patients with upper motor neuron syndrome, e.g., due to stroke. Rectus femoris spasticity is one of the main causes of stiff knee gait and can be treated with botulinum toxin (BoNT‐A) injections. However, previous literature shows large response variations after BoNT‐A treatment between individual participants. These variations could be due to the overestimation of rectus femoris spasticity during gait analyses based on the current main indicator: mid‐swing rectus femoris activity. The objective of this video‐illustrated case series, including gait data of four stroke patients with stiff knee gait, is to propose an alternative explanation for this mid‐swing rectus femoris activity. The presented patients all show mid‐swing rectus femoris activity, which could be considered a sign of spasticity but was interpreted as compensatory activity to improve foot clearance during the swing phase instead. Misinterpretation of compensatory rectus femoris activity as spasticity may lead to inadequate treatment with BoNT‐A injections in some patients, possibly explaining the response variations found in previous literature. Additional biomechanical markers should be explored to better determine the contribution of rectus femoris spasticity in stiff knee in individual patients.